1999
DOI: 10.1016/s0022-5347(05)68276-6
|View full text |Cite
|
Sign up to set email alerts
|

Staging of Prostate Cancer Using 3-Dimensional Transrectal Ultrasound Images: A Pilot Study

Abstract: The 3-D reconstruction of conventional transrectal ultrasonography imaging is superior to 2-D imaging for staging localized prostate cancer. However, this advantage relies entirely on the visibility of prostate cancer lesions on conventional ultrasonography. Further studies are warranted to evaluate this technology for the management of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…To our knowledge we are the first group to evaluate 3D-TRUS for staging prostate cancer in a large group of patients. In a pilot study on 36 patients with newly diagnosed clinically localized prostate cancer, Garg et al [13] used 3D-TRUS with a conventional scanner and no power Doppler US enhancement. They found that 3D-TRUS had an overall staging accuracy of 94%.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge we are the first group to evaluate 3D-TRUS for staging prostate cancer in a large group of patients. In a pilot study on 36 patients with newly diagnosed clinically localized prostate cancer, Garg et al [13] used 3D-TRUS with a conventional scanner and no power Doppler US enhancement. They found that 3D-TRUS had an overall staging accuracy of 94%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a very limited series of 9 patients, the diagnostic accuracy of 3-dimensional TRUS in predicting extraprostatic extension was reported to be superior to that of conventional TRUS. 27 Currently, such variables as the PSA value and Gleason score are used to predict pathologic stage. 6À9 Partin et al 6 reported that the combination of PSA, Gleason score, and clinical stage predicted final pathologic stage best, compared with each variable alone.…”
Section: Discussionmentioning
confidence: 99%
“…In ei ner Pi lot stu die an 36 Pa ti en ten mit neu di ag nos ti zier ten kli nisch lo kal begrenz ten Pros ta ta kar zi nom konn ten Garg et al [29] eine Sta ging ge nau ig keit von 94 nach wei sen. In ih rer Stu die lag die Sen si tivi tät für das lo ka le Sta ging bei 80 und die Spe zi fi tät bei 96 mit ei nem po si tiven Vor her sa ge wert von 90 und ne gati ven Vor her sa ge wert von 96 in der Erken nung der Kap sel über schrei tung.…”
Section: Trans Rek Tale Drei DI Men Sio Na Le So No Gra Phieunclassified